1974
DOI: 10.1037/h0036617
|View full text |Cite
|
Sign up to set email alerts
|

Social decision schemes under risk.

Abstract: 2 A generally satisfactory definition of risk has not yet been proposed (see further the discussion by Coombs & Huang, 1970). Consequently, we will follow the conventions prevalent in the group decision literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Davis 1973, Davis et al 1974, Kerr et al 1975, Laughlin 1980 posits that group interaction is a process where a group maps a distribution of individual ideas and preferences into a collective decision. The theory of social combination models (e.g.…”
Section: Gss Generic Structures and Gss-task ®Tmentioning
confidence: 99%
“…Davis 1973, Davis et al 1974, Kerr et al 1975, Laughlin 1980 posits that group interaction is a process where a group maps a distribution of individual ideas and preferences into a collective decision. The theory of social combination models (e.g.…”
Section: Gss Generic Structures and Gss-task ®Tmentioning
confidence: 99%
“…Laughlin and Sweeney (1977) found that the strategies groups and individuals used in a concept attainment task did not differ but that groups used these strategies more consistently than individuals. Davis, Kerr, Sussmann, and Rissman (1974) found that individuals used four pieces of information to make judgments in a duplex bet task. Groups also used the same pieces of information to make their judgments but used the information in a more reliable fashion.…”
Section: Processingmentioning
confidence: 99%
“…Simple majority, in which the group decision is that favored by more than half of the group members, is the best-fitting social combination process for attitudinal judgments and preferences among bets, especially when the majority position is in the direction of prevailing values or norms (e.g., Cvetkovich & Baumgardner, 1973;Davis, Kerr, Sussmann, & Rissman, 1974;Kerr, Davis, Meek, & Rissman, 1975;Lambert, 1976;Zaleska, 1976Zaleska, , 1978. Attitudinal judgments and preferences among bets are judgmental tasks because they are based on values rather than demonstrably correct answers.…”
Section: Collective Inductionmentioning
confidence: 99%